(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The governance of Higher Education Institutions (HEIs) is a determining factor for the functioning and quality of higher education systems. Several the major challenges facing higher education are related to the quality assurance, governance, and management of HEIs specifically the PHEIs. With the increasing demand for higher education as well as the acknowledgement of its role in promoting economic growth, it becomes more essential to ensure that HEIs are managed in an effective manner. Based on the Higher Education Review Unit (HERU)/National Authority for Qualifications & Quality Assurance of Education & Training (NAQQAET) review findings, a number of the major challenges facing higher education in the Kingdom of Bahrain are related to the quality assurance, governance, and management of HEIs. Most HEIs face challenges in forming their governance structures and activities to be in line with international good practice. In many PHEIs there is a disjuncture between the institution’s vision and mission and its education provision. In addition, there is a blurring between ownership and governance in almost all PHEIs. Furthermore, governance and management structures are generally not clearly outlined, which means that there is a lack of good corporate governance. The researchers identify the factors affecting governance, management, and quality assurance of higher education from stakeholders’ perspectives.